Uji Bioaktivitas Larutan Fermentatif Kulit Pisang Cavendish Terhadap Bakteri Pembusuk Ikan - Junianto Junianto; Reza Salsabila (Samakia : Jurnal Ilmu Perikanan, 2024)
Cavendish banana peels are waste from the banana flour industry. This waste can be used as material for spontaneous lactic acid fermentation. Furthermore, the fermentation solution can be used as a natural preservative. To determine its effectiveness as a natural preservative, it is necessary to know the level of its inhibitory power against the growth of spoilage bacteria. This research aims to determine the effectiveness of the fermentative solution of cavendish banana peel as a compound that inhibits the growth of putrefactive bacteria in fish from the habitat. The research method used is experimental which consists of three stages. The three stages are making a fermentative solution of cavendish banana peel, culturing putrefactive bacteria from fish intestines and testing the inhibitory power. Testing for the inhibition of bacterial activity was carried out using the paper disc diffusion method. The diameter of the clear zone formed around the paper disc is measured and then compared with the classification level of the diameter of the inhibition zone. Based on the results of the research above, it can be concluded that the fermentative solution of cavendish banana peel has an inhibitory effect on the growth of putrefactive bacteria in both tilapia and mackerel. The inhibitory power of tilapia spoilage bacteria is included in the strong inhibition zone classification, while that of mackerel is included in the very strong inhibition zone.